Research in high-energy physics at NSC KIPT (70-th anniversary of lithium nucleus disintegration) - Sorokin, P.V. (Вопросы атомной науки и техники, 2003)
The report delivered at celebration of the 70-th anniversary of work on artificial splitting the lithium nucleus with protons in NSC KIPT